2013
DOI: 10.1021/cm3041357
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Atom and A-Site Vacancy Distributions in Lanthanum Lithium Titanate

Abstract: Lanthanum lithium titanate (LLTO) is one of the most promising electrolyte materials for all-solid-state lithium-ion batteries. Despite numerous studies, the detailed crystal structure is still open to conjecture because of the difficulty of identifying precisely the positions of Li atoms and the distribution of intrinsic cation vacancies. Here we use subangstrom resolution scanning transmission electron microscopy (STEM) imaging methods and spatially resolved electron energy loss spectroscopy (EELS) analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 45 publications
5
86
1
Order By: Relevance
“…45 Furthermore, the Li content, the valence state of Ti and the geometry variation of the oxygen octahedra in the alternating La-rich and La-poor layers were revealed via the associated EELS analysis. 55 The same authors also reported the local structural and chemical variation across the boundaries between the La-rich/poor ordering domains, and they concluded that the domain boundaries serve as obstacles for the Li transport. 49 The precise analysis of the local features provided invaluable insight for interpreting the ionic conduction mechanism.…”
Section: Electrolytesmentioning
confidence: 95%
See 3 more Smart Citations
“…45 Furthermore, the Li content, the valence state of Ti and the geometry variation of the oxygen octahedra in the alternating La-rich and La-poor layers were revealed via the associated EELS analysis. 55 The same authors also reported the local structural and chemical variation across the boundaries between the La-rich/poor ordering domains, and they concluded that the domain boundaries serve as obstacles for the Li transport. 49 The precise analysis of the local features provided invaluable insight for interpreting the ionic conduction mechanism.…”
Section: Electrolytesmentioning
confidence: 95%
“…42,46,47 As a result, the atomic-resolution (S)TEM studies on solid electrolyte materials are quite rare. 44,[47][48][49][50][51][52][53][54][55] Regardless, the limited number of papers have provided unique insight into their ionic conduction behaviors and paved the way for the design and discovery of high-performance solid electrolytes.…”
Section: Electrolytesmentioning
confidence: 99%
See 2 more Smart Citations
“…The (S)TEM studies made important contributions toward this cause. Taking advantage of the sensitivity of annularbright-field (ABF) STEM imaging to light elements such as Li, Gao et al (2013) directly visualized the variation of Li positions in different LLTO polymorphs. Li was observed to reside at the O4 window for the Li-poor composition La0.62Li0.16TiO3, but near the A-site position for the Li-rich composition La0.56Li0.33TiO3.…”
Section: Influence Of Grain Interior Atomic Configuration On Ionic Comentioning
confidence: 99%